Facile Synthesis of Oleanane‐type Pentacyclic Triterpenoids Bearing Hydroxy Groups on D/E Rings. Issue 7 (10th June 2021) - Mu, Tong; Xu, Peng; Yu, Biao
Abstract: Pentacyclic triterpenoids (PTs) comprise one of the largest class of natural products; many bear higher oxidation state on the D/E rings and exhibit a wide range of biological activities. Here, we report the chemical synthesis of a series of oleanane‐type PTs bearing hydroxy groups on D/E rings from the largely available oleanolic acid by transformations following site‐selective C−H hydroxylation. Abstract : Oleanane‐type pentacyclic triterpenoids bearing hydroxy groups at C15, C16, C21, and C22 are effectively synthesized from oleanolic acid by transformations following site‐selective C−H hydroxylation at C16 and C22.